2021
DOI: 10.3390/beverages7020028
|View full text |Cite
|
Sign up to set email alerts
|

Authentication Using Volatile Composition: A Proof-of-Concept Study on the Volatile Profiles of Fourteen Queensland Ciders

Abstract: Although relatively small, the Australian cider industry has experienced significant growth in recent years. One of the current challenges in the industry is the lack of research specific to Australian ciders. Establishing baseline volatile organic compound (VOC) profiles of Australian cider is paramount to developing a better understanding of the industry. This understanding may ultimately be utilized for both the categorization and authentication of existing ciders, and the targeted modification of cider vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 102 publications
(149 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, octanoic and decanoic acids as well as hexanoic acid ethyl ester were also identified as predictors of positive attributes. This is in accordance with the results of Wilson et al, who reported that these compounds are responsible for fruity and fermented odors in ciders.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, octanoic and decanoic acids as well as hexanoic acid ethyl ester were also identified as predictors of positive attributes. This is in accordance with the results of Wilson et al, who reported that these compounds are responsible for fruity and fermented odors in ciders.…”
Section: Resultssupporting
confidence: 94%
“…Extraction of the volatile compounds in the cider was achieved using a simple dichloromethane (DCM) extraction previously used to extract volatile compounds in a range of Queensland ciders [2]. In short, 1.0 mL of DCM was added to 5 mL of each cider sample, and one method was blank (n = 12).…”
Section: Volatile Extraction Proceduresmentioning
confidence: 99%
“…According to a market report published by IBISWorld [1], consumer demand for higher-quality ciders is increasing, and as such, the producer's focus is likely to follow suit. It was suggested by Wilson et al [2] that in order to support the growth of the Australian cider industry, there needs to be a similar growth in research. Given the anticipated demand for higher-quality cider products, research needs to focus on technologies and methods that introduce and improve favourable organoleptic properties, mainly taste and aroma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in popularity is also reflected by the number of scientific papers that were published on this topic in the past decade. Several recent papers deal with flavour properties and volatile compounds of commercially available products [2][3][4][5], of ciders produced from different apple varieties [6,7], or different stages of maturity [6,8], or cider and apple wines produced with varying production strategies [7,[9][10][11][12][13]. In contrast to wine technology, however, in which the impact of grape variety, oenological yeast strains, fermentation strategy or other parameters have been well investigated, there is still a lack of knowledge with respect to the behaviour and the properties of apple wines and ciders.…”
Section: Introductionmentioning
confidence: 99%